2003
DOI: 10.1161/01.cir.0000070547.88378.ea
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravenous Nesiritide on Human Coronary Vasomotor Regulation and Myocardial Oxygen Uptake

Abstract: Background-Nesiritide, recombinant human B-type natriuretic peptide, has been shown to be efficacious in the treatment of decompensated heart failure. The effects of intravenous nesiritide on the human coronary vasculature have not been studied. Methods and Results-Ten patients underwent right and left heart catheterization. Baseline coronary blood flow was determined using quantitative coronary angiography (QCA) and an intracoronary Doppler-tipped guidewire. Myocardial oxygen uptake was measured using a coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 26 publications
3
45
0
1
Order By: Relevance
“…Intravenous thrombolysis or PCI shows better therapeutic effects on acute anterior MI. Since previous studies reported that rhBNP can improve negative left ventricular remodeling and protect left ventricular function (17)(18)(19)(20)(21)(22), we presumed that rhBNP use has better therapeutic effects on acute anterior MI than in other infarction sites. Therefore, we investigated whether rhBNP has beneficial effects on this site, and determined its therapeutic intensity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Intravenous thrombolysis or PCI shows better therapeutic effects on acute anterior MI. Since previous studies reported that rhBNP can improve negative left ventricular remodeling and protect left ventricular function (17)(18)(19)(20)(21)(22), we presumed that rhBNP use has better therapeutic effects on acute anterior MI than in other infarction sites. Therefore, we investigated whether rhBNP has beneficial effects on this site, and determined its therapeutic intensity.…”
Section: Discussionmentioning
confidence: 96%
“…BNP is also a natural factor against cardiac remodeling that regulates the levels of cytokines and inflammatory factors through regulating the expression of fibrosis genes. Furthermore, it directly exerts effects on cardiac fibroblasts to reduce the extracellular matrix of myocardial cells and alleviate interstitial fibrosis and myocardial hypertrophy (18)(19)(20)(21). In addition, BNP selectively expands coronary and lung circulation, increases coronary blood flow and reduces the consumption of myocardial oxygen (22).…”
Section: Discussionmentioning
confidence: 99%
“…natriuretic peptide; brain natriuretic peptide; amino-terminal pro-brain natriuretic peptide; left ventricular hypertrophy BRAIN NATRIURETIC PEPTIDE (BNP) is synthesized in cardiac myocytes as the precursor proBNP, a 108-amino acid peptide (4, 27, 33), and is converted to biologically active peptide BNP32 via a proteolytic cleavage by corin, a type II transmembrane cardiac serine protease (22,38,39). BNP is present in the circulation in two different forms, the biologically active BNP32 that elicits different beneficial cardiorenal and hormonal actions (1,5,8,11,25,26,40) and the amino-terminal portion of BNP (NT-proBNP) that consists of 76 amino acids.In congestive heart failure (CHF) as well as in hypertension (HTN), ventricular cardiomyocytes are progressively recruited to synthesize BNP (24). Whereas initially a successful defensive endocrine response by the heart to preserve cardiorenal homeostasis might occur, a hyporesponsiveness to cardiac peptides, which might contribute in turn to the progression of hypertension, could follow later.…”
mentioning
confidence: 99%
“…BNP is present in the circulation in two different forms, the biologically active BNP32 that elicits different beneficial cardiorenal and hormonal actions (1,5,8,11,25,26,40) and the amino-terminal portion of BNP (NT-proBNP) that consists of 76 amino acids.…”
mentioning
confidence: 99%
“…At 3 h, patients receiving nesiritide had lower PCWP values and decreased dyspnea when compared with controls (14). Finally, both animal (15) and human trials (16) have demonstrated the direct effect of nesiritide infusion on increasing coronary artery blood flow and reducing coronary resistance, ultimately lowering wall stress and myocardial oxygen demands. Additional research will be required to elucidate whether nesiritide is truly a balanced systemic vasodilator.…”
Section: Vasodilationmentioning
confidence: 99%